Juridical Analysis of Administrative Sanctions Against Hospitals Failing to Meet Accreditation Requirements - A.Adhitama; B.Prakoso (International Medical Journal Corp. Ltd, 2026)
Introduction: Hospital accreditation is a critical mechanism to guarantee healthcare quality and patient safety, yet compliance remains a challenge for several institutions. This study examines the legal framework governing hospitals that fail to meet these mandatory accreditation standards. Methods: This research employs a normative juridical method, analyzing statutory regulations, theoretical legal concepts, and authoritative legal literature related to healthcare administration. Results: The findings indicate that while the legal framework outlines clear administrative sanctions—ranging from written warnings to the revocation of operational licenses—the enforcement mechanism faces systemic challenges, including ambiguous regulatory enforcement triggers and regional disparities in oversight. Discussion: The discussion highlights that administrative sanctions serve as a vital instrument of state control (bestuursdwang) to ensure public welfare. However, a significant gap exists between the rigid statutory mandates and the practical economic realities of underfunded regional hospitals, which often leads to lenient enforcement that compromises patient safety. Conclusions: In conclusion, strict enforcement of administrative sanctions is legally justified but must be balanced with proactive state guidance and technical support for struggling facilities. It is recommended that regulatory bodies establish an objective, tiered enforcement protocol and a dedicated support fund to assist non-compliant hospitals in achieving accreditation without disrupting public healthcare access.